Implementation of independent curriculum in Indonesia: Dimensional concept and scope of islamic religious education - Safitri, Amalia Nur Ajeng; Rahman, Arif; Sutarman, Sutarman; Hakim, Ahmad Luqman; Hidayat, Kun (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2024)
This research is motivated by the lack of studies on the implementation of the independent curriculum in Islamic Religious Education. Integrating the independent curriculum with Islamic Religious Education requires compatibility between the two, such as mandatory aspects of the project to strengthen the Pancasila student profile and dimensional aspects and scope of Islamic Religious Education. This research methodology is a qualitative literature type, using a grounded theory approach which is useful as a medium for integrating the two research subjects. The results of this research include the internalization of the independent curriculum in Indonesia regarding the dimensions and scope of Islamic Religious Education, consisting of its adaptive nature, as well as being oriented towards essential material, guided by the values of Islamic teachings, with an emphasis on moral education, as in strengthening Pancasila student profile. Process is supported by the role and participation of stakeholders as well as the use of information technology; (4) Assessments are carried out both routinely and at the end of the program to minimize errors accumulating at the end of the program. Efforts to improve the program are carried out by considering impacts and prioritizing results.